Of white hair and feeding bottles: exploring children-elderly interactions in prehistoric Aegean - Gallou, Chrysanthi (Stavanger Museum, 2018)
Scholarship on age and gender in prehistoric Greece has taken an adult–centric approach with focus placed mostly on young to middle–aged men and women and, as a result, two significant age groups – children and the elderly – have been widely neglected. Lacking a strong insight into attitudes that were shown towards these two age groups, however archaeologists do not really harbour a concept of the whole span of life in the cultures that developed in the Aegean region during the Late Bronze Age. Making children and the elderly visible in the archaeological record and examining their social roles, agency and interactions is vital for a better understanding of the social workings of the prehistoric Aegean world. Integrating an interdisciplinary methodology with a systematic study of the available material remains – ranging from the study of funerary contexts to iconographic sources and textual references, this study seeks to assess the evidence for childhood and old age in Late Bronze Age Aegean, and to shed light - for the first time - on the interactions between the younger and older segments of the population in both life and death from the mid–seventeenth century to the twelfth century BC.